Effect of High Pressure on the Molecular Structure and π-Electrons Delocalization of Canthaxanthin as Revealed by Raman Spectra - Shun-li Ou-Yang; Nan-nan Wu; Yan-jie Tian (Journal of Spectroscopy)
The effect of high pressure on the molecular structure and π-electron delocalization of canthaxanthin was studied by in situ resonance Raman spectroscopy. Changes in the characteristic band frequency and the pressure of canthaxanthin were described. The effect of pressure on π-electron delocalization was also discussed. Results show that the characteristic bands of canthaxanthin increase and reach high wavenumbers. The correlations between Raman frequency of the three main bands and pressure are listed as follows: ν1(C=C) = 3.43P + 1512.3, ν2(C-C) = 3.29P + 1156.1, and ν3(CH3) = 2.16P + 1006.3. The frequency multiplication of canthaxanthin changes as pressure is altered. The pressure effect on the ν1(C=C) mode is more susceptible than on the ν2(C-C) mode, which can be explained by the fact that the β-ring twists to a larger angle from the plane of the conjugated main chain under high pressure, leading to a lower degree of the π-electrons delocalization. The Raman spectra are recovered after the compression-decompression cycle indicating the canthaxanthin has no evident phase change under our experimental conditions.